The Effect of Using Video Tutorial Media on the Interest and Learning Outcomes of Class X Students at Senior High School 1 Padang Gelugur - Wikarya, Yusron; Abhara, Alamin Arseni; B, Ega Harna (International Journal of Educational Dynamics, 2024)
This study investigates the impact of video tutorial media on students' interest and learning outcomes in fine arts, particularly shape drawing, compared to traditional teaching methods. Using a quantitative approach, the study involved pretests, posttests, and questionnaires to measure learning interest indicators interest, attention, motivation, and knowledge as well as learning outcomes. The study population consisted of 317 students, with Class X Natural Sciences 4 as the experimental group and Class X Natural Sciences 5 as the control group, selected through random sampling. The experimental group used video tutorials, while the control group relied on print media and blackboards. Data analysis was conducted using SPSS version 16.0 and Microsoft Excel. Results revealed that the experimental group achieved significantly higher average scores in learning interest (42.52) and learning outcomes (85.39) compared to the control group (33.38 and lower scores, respectively). A significance level of 0.000 (<0.05) confirmed the substantial effect of video tutorials on learning interest and outcomes. The findings highlight that video tutorials enhance students' engagement, comprehension, and motivation, suggesting the need for innovative instructional media in fine arts education to foster better learning experiences.